ACCOUNTING AND CONTROL IN THE MANAGEMENT SYSTEM DEVELOPMENT OF DIGITAL COMMUNICATION ENTERPRISES - VOLYNETS, Oksana; TYCHUK, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the essence of the “digital communications industry” and “digital communications enterprises”. In Ukraine, such enterprises can operate in different segments of the telecommunications market, providing a wide range of communication services for users and businesses. The main types of enterprises in the field of digital communications include telecommunications operators, equipment manufacturers, service providers, software developers, Internet providers, system integrators, consulting and research firms. The number of entities involved in the wireline and wireless communications in Ukraine is analyzed in dynamics. The largest Ukrainian players in the field of electronic communications are presented: mobile operators and Internet providers. Their role has become especially important in times of crisis (epidemic and war).The main directions of management of development of enterprises in the field of digital communications are identified and briefly described: management of assortment and services, organization of procurement of goods and services, organization of accounting and control, management of relations with commercial partners, organization of supply of goods and services, organization of the process of selling services, marketing activities and advertising activities. Accounting and control are key tools in the management system for the development of digital communications enterprises. They provide a number of key functions: accurate reflection of financial transactions, efficiency analysis, control over the use of resources, informed decision-making, and compliance with regulatory requirements. We have identified specific objects of accounting for digital communications enterprises. The features of organization of accounting and control at enterprises of this sphere are formed. The main opportunities provided by control as a key tool in the management system for the development of digital communications enterprises are presented. Thus, an effective system of accounting and control is a prerequisite for the successful development of digital communications enterprises in the context of rapid technological change and growing competition.
Keywords: management; digital communication; telecommunications; enterprise; accounting; control; development efficiency